Actividades lúdicas para el desarrollo psicomotor en los estudiantes de segundo año paralelo ¨A¨ de básica elemental, en la escuela ¨Adolfo Páez¨ en el área de lengua y literatura, del cantón Echeandía, provincia Bolívar periodo 2023 - Colcha, Oscar (2023)
The research work that is presented with the theme, "Playful Activities for Psychomotor Development in students of the second year parallel “A”, of Basic Elementary, in the ¨Adolfo Páez¨ school in the area of Language and Literature, of the canton Echeandía, Bolívar province period 2023. In addition, the general objective was established to determine the relevance of Recreational Activities for Psychomotor Development in students of the second year parallel A of Basic Elementary, at the Adolfo Páez school in the area of Language and Literature, in the canton of Echeandía, Bolívar province period 2023” Therefore, the description of the problem where the shortcomings found in said school are detailed. For this reason, the elaboration of the methodology was applied the qualitative approach and analysis of instruments such as, observation sheet to the 32 second-year students, and the interview with the teacher of the educational school. Finally, a methodological guide made up of five Language and Literature activities was developed, so that teachers take it into consideration and use it as a didactic medium when teaching their classes to make their classes more fun and creative and thus forming the development of critical-reflexive thinking The teacher must take into account playful activities and games as a teaching-learning tool, thus preventing children from being inactive, so they will have free learning with actions that benefit their imagination and creativity.